2018
DOI: 10.1002/jat.3599
|View full text |Cite
|
Sign up to set email alerts
|

Lower sperm quality and testicular and epididymal structural impairment in adult rats exposed to rosuvastatin during prepuberty

Abstract: The increase of obesity, bad eating habits and the lack of physical exercises are highly related to dyslipidemias. Rosuvastatin is a lipid-lowering drug and has been indicated to prevent cardiovascular diseases and to treat dyslipidemias due to its higher efficiency to reduce serum cholesterol concentrations. This study aimed to evaluate the reproductive adverse effects on sexual maturity due to rosuvastatin exposure in juvenile male rats during prepuberty. Three groups were randomly formed with newly weaned r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 75 publications
0
11
0
2
Order By: Relevance
“…Experimental rat studies have reported that statins increase DNA fragmentation in sperm and abnormal sperm rates, while reducing spermatozoa motility [4,5]. Similarly, studies of human males have observed that statins significantly compromise semen quality, particularly sperm motility [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Experimental rat studies have reported that statins increase DNA fragmentation in sperm and abnormal sperm rates, while reducing spermatozoa motility [4,5]. Similarly, studies of human males have observed that statins significantly compromise semen quality, particularly sperm motility [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…The rosuvastatin doses chosen for this study are based on the lowest and highest doses applied in human therapy for children ( Leite et al, 2018a , Leite et al, 2019b , Leite et al, 2018c ), adapted for rodents considering their body surface area, as proposed for Reagan-Shaw et al ( Reagan‐Shaw et al, 2008 ).…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies investigating peri -pubertal rosuvastatin exposure in a rodent experimental model revealed that this drug leads to reproductive impairments in male rats. Rosuvastatin can delay pubertal development, reduce sperm quality, impair spermatogenesis, and alter hormonal signaling ( Leite et al, 2014 , Leite et al, 2018a , Leite et al, 2019b ). Also, rosuvastatin exposure in male rats might affect reproductive function in an intergenerational manner, by damaging ovarian and uterine histophysiology of female offspring ( Leite et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Instead, the negative effects of statins on semen quality characteristics may be due to an alteration in gonadal hormones, mainly testosterone hormone, which is the main controller of spermatogenesis (Banihani, 2018b, 2020; Rogers et al, 2017), and luteinising hormone, which stimulates production of testosterone (Banihani, 2018a; El‐Migdadi, Banihani, & Banihani, 2005). It has been shown that male rats orally administered rosuvastatin at 3 or 10 mg kg −1 day −1 , from postnatal day 21 until preputial, had diminished levels of testosterone, luteinising hormone and follicle‐stimulating hormone (Leite et al, 2014; Leite, Sanabria, et al, 2018). In addition, a study on adult male rats showed that rosuvastatin supplementation at 3 or 10 mg kg −1 day −1 may lead to androgen depletion and germ cell death (Leite et al, 2017).…”
Section: Mechanistic Studiesmentioning
confidence: 99%